2015
DOI: 10.1530/rep-14-0493
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for GSK3 in the regulation of the processes of human labour

Abstract: Preterm birth remains the largest single cause of neonatal death and morbidity. Infection and/or inflammation are strongly associated with preterm delivery. Glycogen synthase kinase 3 (GSK3) is known to be a crucial mediator of inflammation homeostasis. The aims of this study were to determine the effect of spontaneous human labour in foetal membranes and myometrium on GSK3a/b expression, and the effect of inhibition of GSK3a/b on pro-labour mediators in foetal membranes and myometrium stimulated with Toll-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Glycogen synthase kinase 3 (GSK3) activity is increased in fetal membranes after term and preterm labour [51]. In fetal membranes, the GSK3 inhibitor CHIR99021 significantly attenuated TNF-α, IL-1β, IL-6 and IL-8 mRNA expression and secretion induced by the bacterial products and TLR ligands LPS (TLR4 ligand), fsl-1 (TLR2/6 ligand) and flagellin (TLR5 ligand) [51]. The involvement of GSK3 as a regulator of inflammation makes inhibition of GSK3 using synthetic compounds an attractive avenue of research.…”
Section: Targeting Inflammation To Prevent Fetal Membrane Rupturementioning
confidence: 99%
“…Glycogen synthase kinase 3 (GSK3) activity is increased in fetal membranes after term and preterm labour [51]. In fetal membranes, the GSK3 inhibitor CHIR99021 significantly attenuated TNF-α, IL-1β, IL-6 and IL-8 mRNA expression and secretion induced by the bacterial products and TLR ligands LPS (TLR4 ligand), fsl-1 (TLR2/6 ligand) and flagellin (TLR5 ligand) [51]. The involvement of GSK3 as a regulator of inflammation makes inhibition of GSK3 using synthetic compounds an attractive avenue of research.…”
Section: Targeting Inflammation To Prevent Fetal Membrane Rupturementioning
confidence: 99%
“…It has thus been proposed that this represents a “programmed weakening” or “pre-weakening” of the fetal membrane such that it ruptures in the correct area at term, although the mechanical behaviour and failure of this region in vivo remains to be determined. Indeed, a recent review of the current understanding highlighted a cascade of biochemical signalling and expression that leads to “pre-weakening” and can be affected by pro-inflammatory signalling [2325], developing into a “weak zone” above the cervix from which fetal membrane rupture initiates [8]. …”
Section: Introductionmentioning
confidence: 99%
“…These drugs are primarily inhibitors of inflammatory pathway. Their targets included inhibition of NF-κB [5558], enhancers of antiinflammatory peroxisome proliferator activated receptor (PPARs) [59], and antioxidant N-acetyl cysteine[60,61], cytokine suppressive anti-inflammatory drugs [62,63], agents to regulate Glycogen synthase kinase 3 (GSK3), an enzyme crucial for inflammation homeostasis [64], surfactant protein-A and PGJ2 to down regulate TLR mediated inflammation [65,66], targeted IL-6[67], and IL-1β signaling [68] to reduce inflammation, over antiinflammatory suppression using IL-10[6971]. Although many of these (drugs) agents were successful in reducing inflammation or oxidative stress in vitro, some of them were shown to have toxic side effects in animal model trials or in clinical trials, and successful clinical trial outcomes are thus yet to be reported using any of these agents in reducing the risk of PTB.…”
Section: Introductionmentioning
confidence: 99%